Repeated storage of respired carbon in the equatorial Pacific Ocean over the last three glacial cycles. Issue 1 (December 2017) - Jacobel, A.; McManus, J.; Anderson, R.; Winckler, G.
Abstract As the largest reservoir of carbon exchanging with the atmosphere on glacial–interglacial timescales, the deep ocean has been implicated as the likely location of carbon sequestration during Pleistocene glaciations. Despite strong theoretical underpinning for this expectation, radiocarbon data on watermass ventilation ages conflict, and proxy interpretations disagree about the depth, origin and even existence of the respired carbon pool. Because any change in the storage of respiratory carbon is accompanied by corresponding changes in dissolved oxygen concentrations, proxy data reflecting oxygenation are valuable in addressing these apparent inconsistencies. Here, we present a record of redox-sensitive uranium from the central equatorial Pacific Ocean to identify intervals associated with respiratory carbon storage over the past 350 kyr, providing evidence for repeated carbon storage over the last three glacial cycles. We also synthesise our data with previous work and propose an internally consistent picture of glacial carbon storage and equatorial Pacific Ocean watermass structure. During glacial periods the oceans stored carbon removed from the atmosphere, yet identifying precisely where that storage occurred remains challenging. Here, the authors show that the deep equatorial Pacific Ocean was a reservoir for respired carbon during glacial periods for at least the last 350 kyr.